Emotional capital in the lifelong concept of learning - adaptive versus critical approach - Renata Góralska (Wydawnictwo Naukowe Uniwersytetu Mikołaja Kopernika, 2017)
The aim of this article is to formulate the concept of emotional capital. It was first introduced by Benedicte Gendron. It is defined as a set of resources - emotional and social competences - which are significant from the perspective of one's personal, social and professional development. The emotional capital is crucial in the context of the individual's life. It plays a vital role in the day-to-day life of a school child as well as of an adult in a workplace. Moreover, it is a relevant aspect of one's functioning in the local community and in the process of building a civic society. Terms such as human, social and cultural capital are explained in the text. The paper compares two different perspectives on capital's definition: the economic capital which is associated with Robert Putnam, James Coleman and Francis Fukuyama and the social capital connected with the Pierre Bourdieau's theory of capital. The further speculation about an appropriate definition of a social capital was based on these two different approaches. In the summary, the paper points to the educational aspect of a lifelong emotional development.